2023
DOI: 10.1186/s12943-022-01695-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1 attenuates the growth and metastasis of small cell lung cancer through CXCR4/FOXM1/RRM2 axis

Abstract: Background Small cell lung cancer (SCLC) is an aggressive lung cancer subtype that is associated with high recurrence and poor prognosis. Due to lack of potential drug targets, SCLC patients have few therapeutic options. MicroRNAs (miRNAs) provide an interesting repertoire of therapeutic molecules; however, the identification of miRNAs regulating SCLC growth and metastasis and their precise regulatory mechanisms are not well understood. Methods To … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 67 publications
(106 reference statements)
0
13
0
Order By: Relevance
“…However, in cancer cells, DNA damage repair processes, such as nucleotide excision repair, post-replication repair and homologous recombination repair, may counteract the effects of cisplatin, resulting in cisplatin resistance (28). Recent studies have indicated that RRM2, an oncogene, plays a critical role in the proliferation, migration, invasion, and drug resistance of breast cancer cells, small cell lung cancer cells, renal clear cell carcinoma cells, and pancreatic cancer cells (29)(30)(31)(32). In lung adenocarcinoma, suppression of RRM2 also inhibits the proliferation, migration and invasive ability of lung adenocarcinoma cells (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…However, in cancer cells, DNA damage repair processes, such as nucleotide excision repair, post-replication repair and homologous recombination repair, may counteract the effects of cisplatin, resulting in cisplatin resistance (28). Recent studies have indicated that RRM2, an oncogene, plays a critical role in the proliferation, migration, invasion, and drug resistance of breast cancer cells, small cell lung cancer cells, renal clear cell carcinoma cells, and pancreatic cancer cells (29)(30)(31)(32). In lung adenocarcinoma, suppression of RRM2 also inhibits the proliferation, migration and invasive ability of lung adenocarcinoma cells (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the involvement of miRNAs in the regulation of cell proliferation [ 28 , 29 , 30 ]. One of them revealed increased expression of 16 miRNAs and insufficient expression of eight miRNAs in SCLC cell lines and in primary SCLC tumour cells compared to normal lung tissue [ 30 ].…”
Section: Mirnas In Lcmentioning
confidence: 99%
“…Small cell lung cancer (SCLC), a highly aggressive neuroendocrine malignancy, comprises about 15% of bronchogenic carcinomas (1)(2)(3). It is known for its swift progression, propensity for widespread metastasis, and overall dismal prognosis (4,5). Platinumbased chemotherapy combined with etoposide remains the cornerstone of SCLC treatment, delivering an initially favorable response in patients (6,7).…”
Section: Introductionmentioning
confidence: 99%